Chemical Investigation of the Seeds of Echinops echinatus Roxb. - Yadav, R.N.; Kumar Singh, Sujeet (Asian Journal of Chemistry, 2016)
Various carbohydrates and amino acids were obtained by chemical examination of the seeds of Echinops echinatus plant.